2015
DOI: 10.4315/0362-028x.jfp-15-048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Domestic Storage and Thawing Practices on in Poultry-Based Meat Preparations

Abstract: Among consumer food handling practices, time-temperature abuse has been reported as one of the most common contributory factors in salmonellosis outbreaks where the evidence is strong. The present study performed storage tests of burgers, sausages, and kebabs and investigated (i) the effect of refrigerator temperatures (4°C versus 8 or 12°C, which were the temperatures recorded in 33 and 3%, respectively, of domestic refrigerators in Italy), with or without prior temperature abuse (25°C for 2 h, simulating tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…Furthermore, higher temperatures predictably developed a more suitable environment for bacterial proliferation in the samples examined. Storage temperature is the paramount concern relative to proper meat conservation, and food safety authorities worldwide recommend that refrigerated foods be stored between 4 and 5°C in order to prevent or inhibit the growth of spoilage and pathogenic microorganisms (Roccato et al, ). In fact, the literature clearly demonstrated that storing meat at 4°C or below immediately after slaughtering and during transportation is critical for its hygiene, safety and shelf life (Dave & Ghaly, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, higher temperatures predictably developed a more suitable environment for bacterial proliferation in the samples examined. Storage temperature is the paramount concern relative to proper meat conservation, and food safety authorities worldwide recommend that refrigerated foods be stored between 4 and 5°C in order to prevent or inhibit the growth of spoilage and pathogenic microorganisms (Roccato et al, ). In fact, the literature clearly demonstrated that storing meat at 4°C or below immediately after slaughtering and during transportation is critical for its hygiene, safety and shelf life (Dave & Ghaly, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher temperatures predictably developed a more suitable environment for bacterial proliferation in the samples examined. Storage temperature is the paramount concern relative to proper meat conservation, and food safety authorities worldwide recommend that refrigerated foods be stored between 4 and 5°C in order to prevent or inhibit the growth of spoilage and pathogenic microorganisms (Roccato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also point to inappropriate knowledge and practices of consumers in this respect [6,38,44,[51][52][53]. According to Roccato et al [54], thawing, for example, of raw poultry meat overnight at room temperature caused significant increases in the number of Salmonella Typhimurium cases compared to thawing overnight in a refrigerator. Inappropriate knowledge and behavior with regard to frozen products are demonstrated not only by consumers but also by food production and trade professionals [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Tabel 4 juga menunjukkan bahwa hampir semua industri jasa boga belum melakukan pelunakan (thawing) bahan pangan beku (daging) dengan metode yang aman untuk menghindari suhu danger zone sehingga tidak menyebabkan pertumbuhan bakteri patogen, seperti Salmonella Typhimurium, seperti yang dilaporkan oleh Roccato et al (2015). Walaupun thawing pada suhu ruang merupakan metode yang cepat, proses dapat menyebabkan pertumbuhan mikrob patogen apabila suhunya meningkat dan mencapai suhu danger zone (Akhtar et al 2013).…”
Section: Ringkasan Persyaratan (Bobot)unclassified